Development and characterization of PLGA nanoparticles containing 1,3-dihydroxy-2-methylxanthone with improved antitumor activity on a human breast cancer cell line - Maribel, T (2019)
Interest on xanthones has been growing considerably due to their broad spectrum of biological activities. 1,3-Dihydroxy-2-methylxanthone (DHMXAN) showed a significant inhibitory effect on the growth of MCF-7 cancer cells. DHMXAN-loaded nanosphere and nanocapsule formulations were prepared by the solvent displacement technique with the aim of improving the delivery of this poorly water-soluble compound. Moreover, we investigated the usefulness of this nanotechnology-based approach on the improvement of compound's antitumor activity. Nanosphere and nanocapsule mean diameters ranged from 117 +/- 8 to 138 +/- 5 nm and from 266 +/- 7 to 286 +/- 22 nm, respectively, and both systems exhibited negative surface charge. Incorporation efficiency values of DHMXAN in nanospheres and nanocapsules were higher than 30% (30.9 +/- 3.3 to 38.8 +/- 3.6%) and 80% (85 +/- 7 to 88 +/- 6%), respectively. The release study of DHMXAN from nanocapsules suggests that drug release is mainly governed by its partition between the oil core and the external aqueous medium. The effect of different nanoparticulate formulations on the growth of human breast cancer cell line MCF-7 was evaluated using the sulforhodamine B (SRB) assay. Incorporation of DHMXAN in nanospheres and nanocapsules afforded a marked potentiation of the compound inhibitory effect.